1975
DOI: 10.1159/000122438
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Inhibition of Pineal Enzymes in <i>Coturnix </i>Quail

Abstract: The activities of the melatonin-forming enzymes hydroxyindole-O-methyl transferase (HIOMT) and N-acetyl transferase (NAT) were determined in pineals of mature female Coturnix quail receiving implants of melatonin (10 µg, 1 µg, 0.1 µg) weekly for 4 weeks. Both HIOMT and NAT were significantly decreased by implants of 10 and 1 µg melatonin compared to vehicle and intact controls. Oviductal weights tended to be higher with increasing quantities of melatonin. These results suggest that melatonin exerts a feedback … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…This suggests a feedback mechanism where melatonin inhibits its own synthesis [18]. In birds, it also was shown that exogenous melatonin exert a feedback inhibition upon its synthesizing enzymes, HIOMT and AANAT [33]. The mechanism by which melatonin may affect its own synthesis in the trout pineal organ remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests a feedback mechanism where melatonin inhibits its own synthesis [18]. In birds, it also was shown that exogenous melatonin exert a feedback inhibition upon its synthesizing enzymes, HIOMT and AANAT [33]. The mechanism by which melatonin may affect its own synthesis in the trout pineal organ remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…(2005b) observed that melatonin levels were not different at night in O. mykiss fed tryptophan‐supplemented diets, in contrast to what happened during daytime. The authors suggested two hypothesis; either (i) intestinal melatonin production was decreased during the night or (ii) melatonin itself acted in a negative feedback mechanism on pineal hormone synthesis, the second being supported by observations in both birds (Wright & Preslock ) and fish (Yanez & Meissl ). In contrast to O. mykiss , tryptophan did not alter the hormone synthesis in the gut of the D. labrax (Herrero et al .…”
Section: Tryptophan and Melatonin Synthesismentioning
confidence: 95%
“…Several lines of evidence point to a local, intrapineal, role of melatonin. The pineal gland has a high capacity to take up melatonin from the bloodstream (22), and melatonin treatments alter several pineal morphological and biochemical parameters, including the number of dense-cored or granulated vesicles (23,24), thyroxine uptake (25), microtubular protein content (26), enzyme activity in melatonin pathway (26)(27)(28) and noradrenaline (NA) release and uptake (29). It was also early noted that melatonin injections alter 5-HT levels and block the rhythm in 5-HT content of the rat and ferret pineal gland (30,31).…”
mentioning
confidence: 99%